Parameters evaluation for biofertilizer production from mushroom waste through design of experiment - Amir Syarifudin, Baharudin; Norazwina, Zainol; Nor Hazwani, Aziz (Elsevier Ltd, 2025)
The mushroom production industry generates a significant amount of expired mushroom blocks (EMBs), posing economic and environmental challenges. To address this issue, biotechnology research has focused on utilizing EMBs to produce biofertilizers rich in nitrogen and phosphorus. Therefore, this study aimed to evaluate the significant parameters influencing biofertilizer production from mushroom waste through design of experiment approach. Five factors were investigated: mushroom waste (MW) content (70% MW with 30% Bokashi Bran and 30% MW with 70% Bokashi Bran), Bokashi fermentation duration (5–10 days), agitation (presence or absence), waste size (cut or uncut), and drying temperature (60 °C–105 °C). A two-level factorial analysis was used to identify the most influential factors affecting biofertilizer production with high nitrogen and phosphorus content. Both nutrients were measured using a HACH Spectrophotometer. Based on the results, the optimal conditions for high nitrogen content included a drying temperature of 104 °C, 70% mushroom waste content, uncut waste size, and 10 days of fermentation with agitation, yielding 1.62 g/L nitrogen. The optimal conditions for achieving maximum phosphorus content were a drying temperature of 60 °C, 70% mushroom waste content, cut waste, and a 10-day fermentation period without agitation, resulting in a phosphorus concentration of 3.39 g/L. Overall, the best conditions for both nitrogen and phosphorus content were a drying temperature of 80 °C, 70% mushroom waste content, cut waste size, and 10 days of fermentation, with nitrogen and phosphorus contents of 1.10 g/L and 2.61 g/L, respectively. The identifed optimal conditions for producing biofertilizers with high nitrogen and phosphorus content from mushroom waste could offer a sustainable solution to both agricultural and environmental challenges.